Kissing the Wild Woman - Nissen, Christopher (University of Toronto Press, 2011)
Kissing the Wild Woman's analysis of this little-known work adds a new dimension to the study of Renaissance aesthetics in relation to art history, Renaissance thought, women's studies, and Italian literature. Cover – Contents – Acknowledgments – Introduction – 1 The Reformation of the Prose Romance – Bigolina's Cultural Formation – Elements of the Prose Romance – The Plot and Characters of Urania – The Prose Romance according to Boccaccio – Urania in Its Literary Context – Bigolina's Defence of Women – 2 Writing a Portrait – Bigolina and Aretino – Portraiture in Urania – The Caricature of Titian – Of Mirrors, Istoria, and Women in the Arts – 3 Ekphrasis and the Paragone – Ekphrasis in Western Literature – Bigolina and the Paragone – The Judgment of Paris – Descriptio Mulieris – Bigolina's Two Venuses – The Book as Object – 4 The Sight of the Beautiful – Beauty and the Senses in Urania – Sight in the Doctrines of Love – The Body and the Gaze in the Arts – The Woman's Portrait as Gift – 5 Kissing the Wild Woman – Wildness in Urania – Urania's (Nearly) Mad Flight – Femina Salvatica – The Game of the Senses – Conclusion – Appendix: Bigolina's Will in the State Archive of Padua: Text and Translation – Notes – Bibliography – Index – A – B – C – D – E – F – G – H – I – J – K – L – M – N – O – P – Q – R – S – T – U – V – W – X – Z.
Description based on publisher supplied metadata and other sources
Keywords: Bigolina; Giulia; Electronic books; Painting in literature; Aesthetics in literature; Beauty; Personal; in literature; Italy; Civilization; 1559-1789; Bigolina; Giulia; -1569; Urania; nella quale si contiene l'amore d'una giovane di tal nome; English & Italian